Multilayer CuO@NiO Hollow Spheres: Microwave-Assisted Metal–Organic-Framework Derivation and Highly Reversible Structure-Matched Stepwise Lithium Storage - Guo, Wenxiang; Sun, Weiwei; Wang, Yong (ACS nano, 2015)
A unique CuO@NiO microsphere with three-layer ball-in-ball hollow morphology is successfully synthesized by Cu–Ni bimetallic organic frameworks. The beforehand facile microwave-assisted production of the Ni organic framework sphere is used as the template to induce the morphology control of bimetallic oxides. Designed by the controlled surface cationic exchange reactions between Cu and Ni ions, there is an elemental gradient (decreased amount of CuO but increased amount of NiO) from the shell to the core of the microsphere product. This ternary metal oxide hollow structure is found to be very suitable for solving the critical volume expansion problem, which is critical for all high-capacity metal oxide electrodes for lithium ion batteries. A reversible larger-than-theoretical capacity of 1061 mAh·g–1 can be retained after a repetitive 200 cycles without capacity fading compared to the initial cycle. These excellent electrochemical properties are ascribed to the step-by-step lithium insertion reactions induced by the matched CuO@NiO composition from the shell to the core and facilitated lithium/electron diffusion and accommodated volume change in the porous bimetallic oxides microsphere with a multiple-layer yolk–shell nanostructure.